Irisin Is a Positive Regulator for Ferroptosis in Pancreatic Cancer - Bao Chen Yang; Po Sing Leung (Molecular Therapy: Oncolytics, 2020)
Regulated cell death by way of ferroptosis involves iron-dependent accumulation of cellular reactive oxygen species (ROS). Ferroptosis is attracting attention as a potential therapeutic target for cancer treatments without drug resistance. The relationship between irisin, a myokine involved in autophagy and ROS metabolism, and ferroptosis is unclear. In this study, we used erastin-induced ferroptosis in PANC-1 cells to examine potential interactions of irisin with ferroptosis. Using western blots and reverse transcriptase polymerase chain reactions, we found that irisin can further exacerbate erastin-induced upregulation in free iron, lipid ROS levels, and glutathione depletion, relative to cells treated with erastin only. Conversely, removal of irisin limited erastin effects. Furthermore, irisin modulation of ferroptosis was associated with the expression changes in molecules important for ROS metabolism, iron metabolism, and the cysteine/glutamate antiporter system (system Xc−). These study findings suggest that irisin can act as a master factor of ferroptosis, and that potential implications for harnessing irisin-mediated ferroptosis for cancer treatment are warranted.